Services in interworking 3G and WLAN environments. - Axiotis, D.I (IEEE Wireless communications)
Interworking WLANs and 3G mobile networks are expected to provide ubiquitous wireless communications at high data rates and a large variety of services with variable bandwidth and QoS requirements, across a wide range of propagation environments and mobility conditions, using dual mode terminals. The interworking of the two networks is a major step toward a new generation of wireless networks in which other radio technologies are also be integrated. In this article we present possible architectures that enable the interworking of 3G and WLAN networks. We then address the capabilities of various terminal types and describe future services in the interworking environment. Finally, we present market forecasts on terminal and service demand growth.